Antimicrobial use in 20 U.S. beef feedyards: 2018–2019 - Apley, Michael D.; Schrag, Nora F. D.; Amrine, David E.; Lubbers, Brian V.; Singer, Randall S. (Frontiers in Veterinary Science, 2023)
The objective of this study was to continue an initial period of antimicrobial use reporting in a convenience sample of U.S. beef feedyards for the years 2018 and 2019 in addition to adding analysis of the indications for antimicrobial use and outcomes related to these indications. Antimicrobial use is characterized at the study and feedyard levels for a total of 1,141,846 head of cattle in 20 U.S. feedyards. Antimicrobial use is reported as milligrams (mg) of active antimicrobial ingredient per kilogram (kg) of liveweight sold (mg/kg-LW) and regimens of antimicrobials per animal year (Reg/AY). Regimens are described by antimicrobial class within use category as characterized by mg of active antimicrobial product per regimen (mg/Reg) and calendar days of administration per regimen (CDoA/Reg). A total of 1,128,515 regimens of medically important antimicrobials were captured from records. The number of regimens/100 head-in (Reg/100 head-in) are described in a subset of 10 feedyards with adequate data granularity to directly determine indications for antimicrobial administration. For the indications of bovine respiratory disease (BRD), Lameness (Lame), Liver Abscess Control (LAC), and Other (e.g., central nervous system disease, cellulitis) the Reg/100 head-in study-level values are 37.1, 0.8, 98.4, and 0.7, respectively, for 2018, with similar values for 2019. The regimens for BRD are further categorized in these 10 feedyards by the use categories in-feed, control of BRD, and individual animal therapy, yielding study level values of 4.6, 19.6, and 12.9 Reg/100 head-in, respectively, for 2018, with similar values for 2019. Outcomes of therapy for individual animal treatment of BRD, Lame, and Other are reported as treatment success, retreatment, or mortality by 30 days after the initial therapy of an animal for a disease. Treatment success rates (no treatment or mortality in the next 30 days) for 2018 in the 10 feedyards with sufficient data granularity are 76.5%, 86.5%, and 83.0% for BRD, Lame, and Other, respectively. The comparison of these results with other reports of antimicrobial use in North American feedyards highlights how differing approaches in calculating metric values may result in substantially different conclusions regarding antimicrobial use, especially in relation to long-duration uses.